2018
DOI: 10.3389/fvets.2018.00249
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Bioenhancers in Veterinary Phytomedicine

Abstract: Herbal bioenhancers are active phytomolecules that increase the bioavailability, bioefficacy and biological activity of various drugs when coadministered at low concentrations. These valuable compounds reduce the dose, increase the treatment rate, decrease the treatment duration, drug resistance or related adverse reactions which have economical implications in livestock and pet medicine. Eventhough the concept of herbal bioenhancers are known for years through Ayurvedic medicine, the underlying mechanisms rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 78 publications
1
8
0
Order By: Relevance
“…Due to its cytoprotective effects on gastric mucosa through induction of endogenous prostaglandin production, concominant use of Aloe vera and pantoprazole for the gastroesophageal reflux symptoms in mustard gas victims were found to be improved compared to single treatments. (26).…”
Section: Curcuminmentioning
confidence: 99%
“…Due to its cytoprotective effects on gastric mucosa through induction of endogenous prostaglandin production, concominant use of Aloe vera and pantoprazole for the gastroesophageal reflux symptoms in mustard gas victims were found to be improved compared to single treatments. (26).…”
Section: Curcuminmentioning
confidence: 99%
“…and long pepper (Piper longum Linn.) has reduced the gastric first pass effect by inhibiting cytochrome P450 enzymes and P-glycoprotein activities in gut epithelial cells (Yurdakok-Dikmen et al, 2018). Piperine treatment had shown to increase the oral bioavailability of various antibacterial drugs like pefloxacin (Madhukar et al, 2008), gatifloxacin (Patel et al, 2011), amoxicillin (Barve and Ruparel, 2015) and rifampicin (Singh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to low bioavailability, natural products have poor solubility and stability. To overcome these obstacles, bioenhancers of herbal and non-herbal origins are indicated for drugs and phytochemicals [9,10,11]. The use of bioenhancers and potentiators dates back thousands of years [12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In in vivo studies, Yurdakok-Dikmen et al [11] reported that following oral administration, the biodegradation of herbal drugs occurs in the stomach or gut lumen, where membrane permeability and metabolism are key factors in absorption. Bioenhancers are from various classes and exert their effects via multiple mechanisms, such as enzymatic alterations, phytosome formulations, transporter protein alterations, cholagogue/cholerectic effect, and thermogenesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation